Analysis of Students' Ability in Solving Two-Variable Linear Equation System (SPLDV) Questions in Class XI SMA Negeri 1 Siborongborong Academic Year 2019/2020 - Yusniar Nova Tambunan (Jurnal Mantik, 2020)
This study aims to: 1) determine the learning outcomes of class XI IPA-3 students of SMA Negeri 1 Siborongborong in solving math problems on the subject of two-variable linear equations, 2) Knowing the level of understanding of the steps for solving and working on math problems on the subject of linear equations two variables in class XI IPA-3 SMA Negeri 1 Siborongborong. This research uses descriptive method. The subjects of this study were students of class XI IPA-3 at SMA Negeri 1 Siborongborong in the academic year 2019/2020. This research was conducted with the research object of the ability to solve two-variable linear equations system problems. Data obtained from the results of written tests and interviews with several students. The results of this study indicate that the percentage of student learning outcomes in class XI IPA-3 is 28.94%. This percentage was obtained because of the 38 students who took the test, only 11 students scored above the KKM (KKM = 77). This shows that the students' abilities are still low. On the other hand, the level of understanding in solving questions based on Bloom's taxonomy, seen from the description of the answers of all students, shows that students in class XI IPA-3 consist of unistructural levels (28.94%), multistructural (39.47%), relational (21, 05%), and extended abstract (10.52%). Meanwhile, the level of understanding of students based on the results of interviews with several students showed that students in class XI IPA-3 consisted of multistructural, relational, and extended relational levels. Overall, both based on student descriptions and interview results, the level of understanding of class XI IPA-3 students tends to be at the multistructural level.